Marketing and Regulatory Issues for Functional Foods and Nutraceuticals - Rehan Haider; Geetha Das (MultiTech Publisher, 2021)
Functional foods and nutraceuticals have gained substantial attention in recent years due to their potential to offer health benefits beyond basic nutrition. These products bridge the gap between food and pharmaceuticals, offering an appealing solution for health-conscious consumers. However, the marketing of functional foods and nutraceuticals is not without its challenges. One primary concern is regulatory compliance. These products often straddle the line between food and medicine, making it crucial to navigate complex regulatory requirements. Marketing claims, such as